Evaluation of the reduction in central and peripheral arterial blood pressure following an oral glucose load. Issue 42 (October 2017) - Murai, Shunsuke; Takase, Hiroyuki; Sugiura, Tomonori; Yamashita, Sumiyo; Ohte, Nobuyuki; Dohi, Yasuaki
Abstract : Abstract: The clinical significance of measuring central arterial blood pressure has been recently discussed. Although the postprandial reduction in blood pressure is well known, postprandial changes in central blood pressure have not been intensively studied. The present study investigated differences in the reduction of central and peripheral arterial blood pressure after administration of an oral glucose load. An oral glucose tolerance test (75 g) was performed in 360 participants in our physical checkup program. Brachial and central systolic blood pressures were assessed before and after the glucose load. Central arterial blood pressure was measured noninvasively using an automated device. The mean age was 53.6 ± 8.2 years. Both brachial (127.9 ± 17.7 to 125.0 ± 16.3 mm Hg) and central arterial blood pressures were significantly decreased after an oral glucose load (118.9 ± 17.9 to 112.8 ± 16.8 mm Hg). The reduction in blood pressure was greater in central (7.3 ± 11.5 mm Hg) than in brachial blood pressure measurements (3.4 ± 11.3 mm Hg, P < .001). Extreme blood pressure reduction (>20 mm Hg) was recorded more frequently in central (n = 43, 12.3%) than brachial blood pressure measurements (n = 20, 5.6%). An oral glucose load decreases both central and brachial systolic blood pressure, with more pronounced effects on central blood pressure. Postprandial reductions in blood perfusion of the important organs such as the brain may be underestimated when postprandial BP reduction is assessed using brachial BP measurements.